Cerebral Perfusion in Insulin Resistance and Type 2 Diabetes. Issue 1 (January 2015) - Rusinek, Henry; Ha, Jenny; Yau, Po Lai; Storey, Pippa; Tirsi, Aziz; Tsui, Wai Hon; Frosch, Olivia; Azova, Svetlana; Convit, Antonio
Cerebral perfusion was evaluated in 87 subjects prospectively enrolled in three study groups—healthy controls (HC), patients with insulin resistance (IR) but not with diabetes, and type 2 diabetes mellitus (T2DM). Participants received a comprehensive 8-hour clinical evaluation and arterial spin labeling magnetic resonance imaging (MRI). In order of decreasing significance, an association was found between cerebral blood flow (CBF) and sex, waist circumference, diastolic blood pressure (BP), end tidal CO2, and verbal fluency score ( R 2 =0.27, F =5.89, P <0.001). Mean gray-matter CBF in IR was 4.4 mL/100 g per minute lower than in control subjects ( P =0.005), with no hypoperfusion in T2DM ( P =0.312). Subjects with IR also showed no CO2 relationship (slope=−0.012) in the normocapnic range, in contrast to a strong relationship in healthy brains (slope=0.800) and intermediate response (slope=0.445) in diabetic patients. Since the majority of T2DM but few IR subjects were aggressively treated with blood glucose, cholesterol, and BP lowering medications, our finding could be attributed to the beneficial effect of these drugs.